2022
DOI: 10.3390/v14051075
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Environmental Samples of Quarantined Households

Abstract: The role of environmental transmission of SARS-CoV-2 remains unclear. Thus, the aim of this study was to investigate whether viral contamination of air, wastewater, and surfaces in quarantined households result in a higher risk for exposed persons. For this study, a source population of 21 households under quarantine conditions with at least one person who tested positive for SARS-CoV-2 RNA were randomly selected from a community in North Rhine-Westphalia in March 2020. All individuals living in these househol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Oropharyngeal swabs were not consistently collected from infected persons for confirmation of infection and the actual level SARS-CoV-2 shedding in addition to the collection of air samples. Infectiousness of SARS-CoV-2 detected in air was not investigated in most studies ( Chia et al , 2020 ; Guo et al , 2020 ; Liu et al , 2020 ; Conway-Morris et al , 2021 ) or could not be shown ( Döhla et al , 2022 ; Nannu Shankar et al , 2022 ). Infectivity and amount of shed virus have been reported to rapidly decline during the first week after illness onset ( van Beek et al , 2021 ; van Kampen et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oropharyngeal swabs were not consistently collected from infected persons for confirmation of infection and the actual level SARS-CoV-2 shedding in addition to the collection of air samples. Infectiousness of SARS-CoV-2 detected in air was not investigated in most studies ( Chia et al , 2020 ; Guo et al , 2020 ; Liu et al , 2020 ; Conway-Morris et al , 2021 ) or could not be shown ( Döhla et al , 2022 ; Nannu Shankar et al , 2022 ). Infectivity and amount of shed virus have been reported to rapidly decline during the first week after illness onset ( van Beek et al , 2021 ; van Kampen et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Döhla et al emphasized the importance of selecting an appropriate sampling method, as it can influence the stability of viruses in the sample. Since there is no generally recommended virus air sampling method, the choice of air sampler needs to be individually determined based on the specific experimental setup 51 . Most commonly used air samplers for collecting SARS-CoV-2 include filters, impactors, cyclone samplers and impingers 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers may also enter the wastewater network via oral, nasal, or dermal secretions (e.g., during showering/bathing, handwashing, spitting, mouth washing, nasal irrigation). For example, a recent SARS-CoV-2 study identified viral RNA in washbasin and shower siphons of households containing known COVID-19 cases, 54 and modeling has suggested that sputum can be a major source of SARS-CoV-2 in wastewater. 55 Although the ability of WBE to detect biomarkers predominantly present in nonurinary/fecal sources is an area requiring more attention, it would seem likely that the detection of such biomarkers will be influenced by the scale of the monitoring, with community-level monitoring less likely to detect these biomarkers compared with neighborhood- or building-level monitoring.…”
Section: Discussionmentioning
confidence: 99%